Influence of harvesting stages on seed quality characteristics and seed yield in soybean (Glycine max (L) Merrill): Influence of harvesting stages on seed quality characteristics and seed yield in soybean (Glycine max (L) Merrill) - P V PATIL; S S NICHAL; M S DANDGE; V V TAPRE (Journal of Oilseeds Research, 2023)
The experiment was conducted with an objective of knowing the proper stage of harvesting in soybean. The treatments consisting five genotypes with three harvesting stages viz., physiological maturity (H1), five days after physiological maturity (H2), and field maturity (H3). The seed moisture content, hundred seed weight, seed size, germination, root length, shoot length, vigour index, seedling weight, seedling dry weight and seed yield were maximum at physiological maturity stage. Among the genotypes, AMS 100-39 was found to be best genotype for seed/crop production. All seed and seedling vigour components attained maximum values at physiological maturity stage and decreased at subsequent stages of harvesting after physiological maturity. Hence, it is advisable to harvest the soybean crop at physiological maturity stage.